Le subside gouvernemental alloué aux Bollandistes (1837-1869): Histoire d'un enjeu idéologique, (I) - Joassart, Bernard (Analecta Bollandiana, 2024)
As soon as it was reestablished in 1837, the Bollandist Society received an annual subsidy from the Belgian government: it was a "national" high-quality work. But very soon, voices were raised, particularly within the liberal political world, against this subsidy: was it necessary for the government to support such a Jesuit-run enterprise? Often called into question, the grant was finally abol-ished in 1869. Though costing the state very little, this affair reflected, among other things, the opposition between the two major political tendencies of the time - Catholics and Liberals -, which, over the decades, put an end to the unionism of 1830. Not to mention the "fear of the Jesuits".